Analysis of Reading Comprehension Difficulties Among Fourth-Grade Elementary School Students - Lillatusyika, Zahwa; Ain, Siti Quratul (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This descriptive qualitative study examines the implementation of a culture of shame in shaping the character of teacher discipline at MAPN 4 Medan. The culture of shame, which is based on social norms, stresses responsibility for mistakes. Data were collected through observation, in-depth interviews, and documentation studies, involving the principal, vice principal, teachers, and administrative staff. Data analysis followed four stages: collection, reduction, presentation, and drawing conclusions. The results showed that the implementation of a culture of shame at MAPN 4 Medan has been effective, although not yet fully integrated. Socialization was carried out through moral training, motivational programs, and instilling the values ​​of a culture of shame. These initiatives aim to build teacher discipline and strengthen moral identity, leading to increased responsibility and professionalism. Positive changes observed include a decrease in rule violations and tardiness. Despite obstacles such as cultural resistance, the overall approach to cultivating shame accompanied by motivation positively affects the character of discipline and moral identity, encouraging greater discipline, responsibility, and professionalism, although individual awareness is still needed.